Children's unscheduled primary and emergency care in Ireland: a multimethod approach to understanding decision making, trends, outcomes and parental perspectives (CUPID): project protocol. Issue 8 (13th August 2020) - McAuliffe, Eilish; Hamza, Moayed; McDonnell, Thérèse; Nicholson, Emma; De Brún, Aoife; Barrett, Michael; Brunsdon, Christopher; Bury, Gerard; Collins, Claire; Deasy, Conor; Fitzsimons, John; Galligan, Marie; et al.
Abstract : Introduction: The aim of this project is to determine the patterns, decision-making processes and parental preferences associated with unscheduled paediatric healthcare utilisation in Ireland. Unscheduled paediatric healthcare is outpatient care provided within primary care settings by general practitioners (GPs), emergency departments (EDs) located in paediatric and general hospitals, and out-of-hours services provided by cooperatives of GPs operating on a regional basis. This project will take a multimethod approach to analysing the utilisation of unscheduled paediatric healthcare nationally within the context of a significant change to the provision of healthcare for young children in Ireland—the introduction of free at the point of delivery GP care for all children aged under 6. Methods and analysis: A multimethod approach consisting of three work packages will be employed. Using patient-level data, work package 1 will describe patterns of attendance at primary care, out-of-hours medical services and at EDs. Applying a difference-in-difference methodology, the impact of the introduction of free GP care for children under 6 on attendance will be assessed. Work package 2 will explore geospatial trends of attendance at EDs, identifying disparities in ED attendance by local area and demographic characteristics. Work package 3 will employ two discrete choice experiments to examine parental preferences for unscheduled paediatric healthcare and GP decision making when referring a child to the ED. The insights gained by each of the work packages individually and collectively will inform evidence-based health policy for the organisation of paediatric care and resource allocation. Ethics and dissemination: Ethical approval for this research has been granted by University College Dublin, The Irish College of General Practitioners and the five participating hospitals. Results will be disseminated via publication in peer-reviewed journals, national and international conferences, and to relevant stakeholders and interest groups.